2011
DOI: 10.1007/s11274-011-0869-1
|View full text |Cite
|
Sign up to set email alerts
|

Hairy root cultures of butterfly pea (Clitoria ternatea L.): Agrobacterium × plant factors influencing transformation

Abstract: Transformed rhizoclones were developed from Agrobacterium-treated explants of the medicinally important twinning legume Clitoria ternatea L. Several key factors influencing transformation events were optimized. A4T was the most infectious among the strains employed. Internode segments were more responsive than leaves, outdoor-grown explants preferred to those from in vitro cultures. High frequency transformation, resulting in up to 85.8% rhizogenesis, was attained using pre-pricked internodal explants for imme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…In our study, it was found that immersing pre-pricked explants of B. diffusa in A. rhizogenes suspension was the most suitable method for achieving the highest transformation efficiency, regardless of Agrobacterium strains employed. This was in conformity with that for C. ternatea (Swain et al 2012). The influence of phenolic compounds secreted from the wound sites of explants on throughput of transformed tissues has been discussed earlier.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, it was found that immersing pre-pricked explants of B. diffusa in A. rhizogenes suspension was the most suitable method for achieving the highest transformation efficiency, regardless of Agrobacterium strains employed. This was in conformity with that for C. ternatea (Swain et al 2012). The influence of phenolic compounds secreted from the wound sites of explants on throughput of transformed tissues has been discussed earlier.…”
Section: Discussionsupporting
confidence: 89%
“…Internode segments of garden-grown explants were preferred to those from in vitro cultures; this is in conformity with another important medicinal plant, butterfly pea (Clitoria ternatea; Swain et al 2012). The transformation efficiency could also vary in response to different pathogenic strains of A. rhizogenes (Pal et al 2013;Rao et al 2012).…”
Section: Discussionmentioning
confidence: 91%
“…The hairy root induction are influenced by several factors, such as Agrobacterium rhizogenes strains, the addition of growth regulators on the media, parts of the plant are used as explants, and the density of bacteria (Ermayanti et al, 2009;Lee et al, 2010;Swain et al, 2011). The research was carried out by Chakravarty & Pruski (2010) showed that OD 600 = 0.2 could improve significantly the average efficiency transformation of Agrobacterium rhizogenes on potato.…”
Section: Induction Of Hairy Roots By a Rhizogenesmentioning
confidence: 99%
“…Transgenic shoots were obtained on the selective media after 4 months in tissue culture and their transgenic status was confi rmed through GUS assay and PCR analysis. During further study efforts were made to optimise various factors governing the maximum transformation effi ciency during hairy root cultures in C. ternatea (Swain et al 2012a ). Among the four different strains of A. rhizogenes (A4, A4T, 8196, LBA 9402) employed, the highest transformation efficiency was obtained with A4T type of strain.…”
Section: Clitoria Ternatea Lmentioning
confidence: 99%